Determinants of mobile technology use and smartphone application interest in cancer patients. (2nd October 2018) - Raghunathan, Nirupa Jaya; Korenstein, Deborah; Li, Qing S.; Tonorezos, Emily S.; Mao, Jun J.
Abstract: Background: Supportive care is a critical component of the treatment of cancer patients that is underutilized; patient lack of information about these services is an important barrier. Mobile technologies may be useful tools for delivering information, but cancer patient use of and interest in using them to learn about supportive care services have not been described. This study evaluates factors associated with cancer patient use of mobile technologies and interest in smartphone applications for information delivery about supportive care. Methods: We conducted a cross‐sectional survey among cancer patients from one urban academic hospital and 11 community hospitals. Patients self‐reported use of mobile technologies and interest in smartphone applications. Multivariate logistic analysis was used to identify determinants of mobile technology use and smartphone interest. Results: Among 631 participants, 466 (74%) reported regular use of mobile devices and 242 (39%) expressed an interest in supportive care information via smartphone applications. Patients under 45 were more likely to use a mobile device (Adjusted Odds Ratio [AOR] 6.8, 2.8‐16.9 95% CI, P  < 0.001) and were interested in smartphone applications for delivery of information (AOR 3.2, 1.8‐5.9 95% CI, P  < 0.001). Non‐white patients had similar use of mobile technology compared to whites but reported greater interest in smartphone application‐based information (AOR 3.4, 2.1‐5.5 95% CI, P  < 0.001). Conclusion: Many patients expressed interest in smartphone application‐based information about supportive care services, especially those who are younger and non‐white. Future studies should investigate the characteristics of patients and smartphones applications that will optimize information delivery through a mobile technology platform. Abstract : This study assesses the demographic and treatment‐related characteristics associated with mobile technology use and smartphone application interest in a mixed patient population from academic and community settings. It was found that age and race impact mobile technology use and interest in smartphone applications with younger and non‐white populations expressing an interest in smartphones at three times the reference group.